2012
DOI: 10.1128/jb.06304-11
|View full text |Cite
|
Sign up to set email alerts
|

The Polyketide Pks1 Contributes to Biofilm Formation in Mycobacterium tuberculosis

Abstract: Infections caused by biofilms are abundant and highly persistent, displaying phenotypic resistance to high concentrations of antimicrobials and modulating host immune systems. Tuberculosis (TB), caused by Mycobacterium tuberculosis, shares these qualities with biofilm infections. To identify genetic determinants of biofilm formation in M. tuberculosis, we performed a small-scale transposon screen using an in vitro pellicle biofilm assay. We identified five M. tuberculosis mutants that were reproducibly attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 42 publications
(44 reference statements)
1
75
0
1
Order By: Relevance
“…Biofilm formation in mycobacteria is multifactorial, and the roles of GPLs and free mycolates in biofilm formation by M. smegmatis have been demonstrated (10,11,13,33). Although the role of extracellular lipids in mycobacterial biofilm formation has been established, a recent genetic screen demonstrated that M. tuberculosis biofilm formation also requires a number of additional factors that are not limited to cell wall lipid biosynthesis or transport (37). It is unknown whether homologs of these proteins also play a role in M. smegmatis biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm formation in mycobacteria is multifactorial, and the roles of GPLs and free mycolates in biofilm formation by M. smegmatis have been demonstrated (10,11,13,33). Although the role of extracellular lipids in mycobacterial biofilm formation has been established, a recent genetic screen demonstrated that M. tuberculosis biofilm formation also requires a number of additional factors that are not limited to cell wall lipid biosynthesis or transport (37). It is unknown whether homologs of these proteins also play a role in M. smegmatis biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the extent to which rifampin resistance alters PDIM structures or concentrations or controls remodeling of other biochemical components of the multilayered cell wall remains unknown. Cell wall lipids, particularly cell surface polyketides, interface directly with the host and regulate immunogens that are exposed to the host (14) and have been known to control the permeability of the organism (15)(16)(17)(18) in ways that might affect the transport of other drugs. Also, if these candidate cell wall changes can be reproducibly associated with drug resistance phenotypes, then altered lipids might also function as biochemical markers of the drug-resistant state (19).…”
mentioning
confidence: 99%
“…There are numerous diverse forms, ranging from microcolonies on submerged substrata to pellicles at air–medium interfaces [1–4]. biofilms develop through genetically programmed pathways and harbor phenotypically heterogeneous but genetically clonal populations of constituent cells [5–16]. Microbial biofilms display a variety of behaviors that are not associated with dispersed planktonic growth, including tolerance to environmental and immunological stresses and antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%